Attitudes toward equality of outcomes and opportunities: A within-country analysis - Karonen, Esa; Lievore, Ilaria (Map i neq deliverables. Turku: INVEST Research Flagship Centr e / University of Turku, 2025)
This research aims to contribute providing new evidence on individual attitudes toward equality, studying individual attitudes on equality of opportunities and equality of outcome in several European countries, and focusing both on how different factors affect differences between European countries as well as on differences within countries at the regional level. We use the European Social Survey’s years 2008 and 2016 along with other data sources to within-country differences, by focusing on regional-, individual-, and economic factors. The main results show, that both country- and regional-level variance in the equality attitudes were equally significant. Over time, we found that attitudes toward both equality of outcomes and opportunities attitudes have become stronger, yet opinions have become more fragmented. Countries that share similar systems, seem to be also similar in equality attitudes. On specific factors, we found that economic variables with political alignment were important in people’s attitudes on equality, while on a regional level higher economic output decreases agreement with equality of outcome.